Method Verification of Carbon and Sulfur Determination in Ferronickel Tapping Samples Using HCS-801 in Accordance with GB/T 20123 - Muh. Azis Albar. J; Muhammad Mattana Anwar; Ardiansah Ardiansah; Mahardika Sandy Ponco; Alexander Malau (Candela Edutech Indonesia, 2026)
Reliable determination of carbon (C) and sulfur (S) in tapping ferronickel is critical for metallurgical quality control and compliance with industrial specifications. Given the complex metallic matrix of ferronickel, verification of analytical performance is essential before routine application. This study verifies the GB/T 20123 standard method for the simultaneous determination of carbon and sulfur in tapping ferronickel using a High Carbon Sulfur (HCS-801) combustion–infrared analyzer. Method performance was assessed using accuracy, precision (repeatability), linearity, limit of detection (LOD), and limit of quantification (LOQ), in accordance with internationally accepted validation principles. Evaluation of recovery testing yielded 97.82 % for carbon and 99.04 % for sulfur, both within acceptable recovery ranges. Precision expressed as %RSD was 1.27% for carbon and 0.70% for sulfur, complying with the Horwitz criterion (% RSD < ½ CV Horwitz) and the general acceptance limit of 2 %. Excellent linearity was obtained across the calibration range, with correlation coefficients (r) of 0.998 for carbon and 0.9984 for sulfur. LOD and LOQ values, calculated based on the standard deviation of response and slope of calibration curves, were 0.0557% and 0.1855% for carbon, and 0.0123 % and 0.0409 % for sulfur, respectively. The results demonstrate that the GB/T 20123 method, when implemented with the HCS-801 analyzer, provides reliable analytical performance for carbon and sulfur determination in tapped ferronickel and is suitable for routine industrial applications.